ChemInform Abstract: Direct Carboxylation of Aryl Tosylates by CO2 Catalyzed by in situ‐Generated Ni0. Issue 29 (29th June 2016) - Rebih, Fatima; Andreini, Manuel; Moncomble, Aurelien; Harrison‐Marchand, Anne; Maddaluno, Jacques; Durandetti, Muriel
Abstract: The mild, convenient and user‐friendly process tolerates multiple functional groups.